2023
DOI: 10.1093/mnras/stad2581
|View full text |Cite
|
Sign up to set email alerts
|

The VLT MUSE NFM view of outflows and externally photoevaporating discs near the orion bar★

Thomas J Haworth,
Megan Reiter,
C Robert O’Dell
et al.

Abstract: We present VLT/MUSE Narrow Field Mode (NFM) observations of a pair of disc-bearing young stellar objects towards the Orion Bar: 203-504 and 203-506. Both of these discs are subject to external photoevaporation, where winds are launched from their outer regions due to environmental irradiation. Intriguingly, despite having projected separation from one another of only 1.65″(660 au at 400 pc), 203-504 has a classic teardrop shaped “proplyd” morphology pointing towards θ2Ori A (indicating irradiation by the EUV o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 140 publications
0
3
0
Order By: Relevance
“…Recent ALMA surveys in Orion have also found indirect evidence of external photoevaporation in intermediate-UV environments, revealing that disks close to B-and A-type stars are on average ∼2-4 times less massive than the disks farther away from B-and A-type stars (van Terwisga et al 2019;van Terwisga & Hacar 2023). Despite these findings, identifying direct signatures of external photoevaporation has proven challenging outside of the >10 4 G 0 regions of the ONC and other O-star-hosting clusters, where many disks are exposed not only to intense FUV irradiation but also to intense EUV irradiation that can externally ionize FUV-driven photoevaporative winds to the point where large samples of ionized winds become bright and easy to see with the VLA (e.g., Churchwell et al 1987;Garay et al 1987;Felli et al 1993aFelli et al , 1993bForbrich et al 2016;Sheehan et al 2016), HST (e.g., O'dell & Wen 1994;Bally et al 1998Bally et al , 2000Ricci et al 2008;Smith et al 2010;Fang et al 2012;Haworth et al 2021), VLT/MUSE (e.g., Haworth et al 2023;Aru et al 2024), JWST (Berné et al 2022;Habart et al 2023;McCaughrean & Pearson 2023), and ALMA (Ballering et al 2023).…”
Section: Disk Photoevaporation In An Intermediately Irradiated Star-f...mentioning
confidence: 99%
See 2 more Smart Citations
“…Recent ALMA surveys in Orion have also found indirect evidence of external photoevaporation in intermediate-UV environments, revealing that disks close to B-and A-type stars are on average ∼2-4 times less massive than the disks farther away from B-and A-type stars (van Terwisga et al 2019;van Terwisga & Hacar 2023). Despite these findings, identifying direct signatures of external photoevaporation has proven challenging outside of the >10 4 G 0 regions of the ONC and other O-star-hosting clusters, where many disks are exposed not only to intense FUV irradiation but also to intense EUV irradiation that can externally ionize FUV-driven photoevaporative winds to the point where large samples of ionized winds become bright and easy to see with the VLA (e.g., Churchwell et al 1987;Garay et al 1987;Felli et al 1993aFelli et al , 1993bForbrich et al 2016;Sheehan et al 2016), HST (e.g., O'dell & Wen 1994;Bally et al 1998Bally et al , 2000Ricci et al 2008;Smith et al 2010;Fang et al 2012;Haworth et al 2021), VLT/MUSE (e.g., Haworth et al 2023;Aru et al 2024), JWST (Berné et al 2022;Habart et al 2023;McCaughrean & Pearson 2023), and ALMA (Ballering et al 2023).…”
Section: Disk Photoevaporation In An Intermediately Irradiated Star-f...mentioning
confidence: 99%
“…Given the potential prevalence of internally illuminated disk winds in NGC 1977, it is worth pointing out that externally driven but internally illuminated disk winds can have similar morphologies as externally driven and externally illuminated winds. The d203-506 disk in the Orion Bar, for example, is irradiated by a ∼10 4 G 0 FUV field but shielded from the external EUV field (e.g., Champion et al 2017), and recent infrared-and submillimeter-wavelength imaging of this disk has revealed that the photoevaporative wind surrounding d203-506 has the same cometary shape as the externally illuminated ONC proplyds (e.g., Haworth et al 2023;Berné et al 2024). This new imaging demonstrates that anisotropic FUV radiation fields play a dominant role in sculpting cometary wind morphologies when an external EUV radiation field is not present.…”
Section: Proplyd Illumination Sources In Ngc 1977mentioning
confidence: 99%
See 1 more Smart Citation